LAYANAN BIMBINGAN KELOMPOK DENGAN TEKNIK HOMEROOM UNTUK MENINGKATKAN SELF REGULATED LEARNING SISWA KELAS VIII SMPN 3 PADALARANG - Abdullah, Ifni Nurhanifa; M Afrillianto; Rismawati Siddik, Riesa (FOKUS : Kajian Bimbingan dan Konseling dalam Pendidikan, 2024)
This research was conducted to test the effectiveness of group guidance services using the Homeroom technique to improve self-regulated learning for Grade VIII students ofSMPN 3 Padalarang. Self Regulated Learning is the ability of students to know their learning potential, and if the student has Self Regulated Learning, he can set what learning goals he wants to achieve. Group guidance in this study can be interpreted as a service provided by a counseling teacher to a group of students in class VIII at junior high school, which aims to enable students to improve their self-regulated learning. The results showed that after being given the group guidance service process using the Homeroom technique, there was an increase. This is evident from the results of the post test given after the service process, group guidance services using the Homeroom technique have proven to be effective in increasing the Self Regulated Learning of class VIII students at SMPN 3 Padalarang.